Dyslipidemia and risk of prostate canсer in patients with urologic diseases - A. V. Smirnov; O. V. Gruzdeva; E. V. Pomeshkin; A. I. Bragin-Maltsev (Фундаментальная и клиническая медицина)
Aim. To assess the impact of homeostasis parameters on risk of prostate cancer.Materials and Methods. The study included 108  patients with urologic diseases and with (n = 54) or without (n = 54) prostate cancer. Median age in both groups was 67 (interquartile range 64-73) years. Clinicopathological data and blood test results have been collected from outpatient and inpatient records. In particular, we measured serum levels of total testosterone and prostate-specific antigen.Results. Risk factors for prostate cancer include increased total cholesterol (p = 0.023), low-density lipoprotein cholesterol (p = 0.035), total triglycerides (p = 0.048), and total testosterone (p = 0.002). High levels of total testosterone directly correlated with the tumor stage (r = 0.56). The concentration of prostate-specific antigen correlated with the lipid parameters and remained a reliable diagnostic criterion (p = 0.002).Conclusion. The association of hyper/dyslipidemia with prostate cancer provides an opportunity to improve its prevention by routine lipid screening in high-risk groups.